Impervious surface cover and number of restaurants shape diet variation in an urban carnivore - Tal Caspi; Monica G. Serrano; Stevi L. Vanderzwan; Janet Kessler; Christopher J. Schell; Benjamin N. Sacks (Ecosphere)
Abstract In the past decade, studies have demonstrated that urban and nonurban wildlife populations exhibit differences in foraging behavior and diet. However, little is known about how environmental heterogeneity shapes dietary variation of organisms within cities. We examined the vertebrate prey components of diets of coyotes (Canis latrans) in San Francisco to quantify territory‐ and individual‐level dietary differences and determine how within‐city variation in land cover and land use affects coyote diet. We genotyped fecal samples for individual coyote identification and used DNA metabarcoding to quantify diet composition and individual niche differentiation. The highest contributor to coyote diet overall was anthropogenic food followed by small mammals. The most frequently detected species were domestic chicken, pocket gopher (Thomomys bottae), domestic pig, and raccoon (Procyon lotor). Diet composition varied significantly across territories and among individuals, with territories explaining most of the variation. Within territories (i.e., family groups), the amount of dietary variation attributed to among‐individual differences increased with green space and decreased with impervious surface cover. The quantity of anthropogenic food in scats also was positively correlated with impervious surface cover, suggesting that coyotes consumed more human food in more urbanized territories. The quantity of invasive, human‐commensal rodents in the diet was positively correlated with the number of food services in a territory. Overall, our results revealed substantial intraspecific variation in coyote diet associated with urban landscape heterogeneity and point to a diversifying effect of urbanization on population diet.